APLIKASI FARMAKOTERAPI SISTEM PAKAR BERBASIS WEB UNTUK MENDIAGNOSA PENYAKIT SYARAF PUSAT - Paryati Paryati (Seminar Nasional Informatika (SEMNASIF), 2015)
Central nervous system has the main function to detect, analyze, and deliver information. The information collected by the sensory system is integrated in the brain, the signal is passed to the motor system, the autonomic pathways to control movement, visceral activity, and endocrine functions. The nervous system has immune function and support modulate neural activity. Neurological disease commonly found due to the lack of information and knowledge about the disease. So, this study made by using forward and backward chaining reasoning with healing therapies and the treatment. The system is made so that the patient can see, understand the type of central nervous diseases, their healing therapies and the treatment. This system provides multiple solutions for the prevention of disease according to the type of illness. The methodology for developing the system is using waterfall method. The application software used to create this application program is Dreamweaver MX, XAMPP, Adobe Photoshop, MySQL, Opera / Mozilla Firefox. The results of this research is in the form of an application program that can help user to determine the type of central nervous diseases, provide extensive information about central nervous diseases, the treatment and healing therapy.